Analisis Keputusan Masyarakat Muslim Desa Salam Buku dalam Memilih Bank Konvensional daripada Bank Syariah di Bangko - Zilla Zilla; Maulana Yusuf (Lembaga Yasin AlSys, 2026)
Although Islamic banking continues to develop as an alternative financial service based on Islamic principles, conventional banking remains the primary choice for some rural Muslim communities in conducting daily financial transactions. This study aims to analyze the factors influencing the decisions of the Muslim community of Salam Buku Village in choosing conventional banks and to identify efforts that can be made to increase public interest in Islamic banks. This study used a qualitative approach with a descriptive method, involving 35 informants from the Salam Buku Village community selected based on their involvement in using banking services. Data were collected through observation, interviews, and documentation, and were then analyzed through the stages of data reduction, data display, and conclusion drawing. The results showed that the community’s decision to choose conventional banks was influenced by low knowledge of Islamic banks, occupational demands, comfort with the facilities and services of conventional banks, limited promotion of Islamic banks, and social influence from the surrounding environment. These findings confirm that Islamic financial literacy and direct outreach to rural communities are important factors in increasing understanding of and interest in Islamic banking services. The implications of this study provide practical contributions for Islamic banks in designing literacy, promotion, and service approach strategies that are more effective and aligned with the needs of rural Muslim communities.